The Impact of Age-Specific Minimum Wages on Youth Employment and Education: A Regression Discontinuity Analysis - Meltem Dayioglu-Tayfur; Muserref Kucukbayrak; Semih Tumen (Institute of Labor Economics (IZA), 2020)
We exploit an age-specific minimum wage rule – which sets a lower minimum wage for workers of age 15 than that for workers of age 16 and above in Turkey – and its abolition to estimate the causal effect of a minimum wage increase on youth employment and education. Using a regression discontinuity design in tandem with a difference-in-discontinuities analysis, we find that increasing the minimum wage substantially reduces the employment of young males. In terms of magnitudes, the employment probability declines by 2.5-3.1 percentage points at the 16-year-old age cut-off. Moreover, the probability of unemployment increases approximately 2 percentage points. We also document that the minimum wage hike does not generate a major change in high school enrollment, while the likelihood of transitioning into "neither in employment nor in education and training" (NEET) category notably increases among young males. We argue that the effects of the policy have mostly been driven by the demand-side forces rather than the supply side.
Keywords: J21; J24; J31; J38; 330; education; youth employment; age-specific minimum wages; regression discontinuity design